2020
DOI: 10.1155/2020/5246350
|View full text |Cite
|
Sign up to set email alerts
|

Feature of Heart Rate Variability and Metabolic Mechanism in Female College Students with Depression

Abstract: Purpose. To explore the effects of depression on cardiac autonomic nerve function and related metabolic pathways, the heart rate variability (HRV) and urinary differential metabolites were detected on the college students with depression. Methods. 12 female freshmen with depression were filtered by the Beck Depression Inventory (BDI-II) and Self-rating Depression Scale (SDS). By wearing an HRV monitoring system, time domain indexes and frequency domain indexes were measured over 24 hours. Liquid chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…It has already been shown that young people with depression also show impairment of autonomic nervous system functions, high levels of stress, and have slow fatigue recovery. Researchers have proposed that there are numerous metabolic pathways disrupted in young people with depression, including coenzyme Q biosynthesis, steroid metabolism, tyrosine metabolism, glycine-serine-threonine metabolism and pyrimidine metabolism [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has already been shown that young people with depression also show impairment of autonomic nervous system functions, high levels of stress, and have slow fatigue recovery. Researchers have proposed that there are numerous metabolic pathways disrupted in young people with depression, including coenzyme Q biosynthesis, steroid metabolism, tyrosine metabolism, glycine-serine-threonine metabolism and pyrimidine metabolism [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The physiological effects of Coenzyme Q include reducing free radical production in the myocardium and muscle, and improving physical performance in people with heart disease [ 41 , 42 ]. A study found that the relative level of 4-hydroxyphenyl lactic acid, the key metabolite in the pathway of coenzyme Q biosynthesis, was significantly decreased in the depression group, indicating that metabolic deficiencies may contribute to depression [ 41 ]. Corticosterone is a key substance in the steroid hormone biosynthesis pathway and has been associated with obesity and metabolic disorders [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of the pathogenesis of depression mainly involves neurobiological research. It is generally believed that the etiology of depression is related to neuroendocrine disorders, neurotransmitter concentration changes, autonomic dysfunction, and changes in the function of cognitive-related brain areas [6][7][8][9]. Therefore, it is very important to analyze the changes in the brain function of college students with depression to reveal its pathogenesis.…”
Section: Introductionmentioning
confidence: 99%